KAI2-KL signaling intersects with light-signaling for photomorphogenesis. (3rd April 2019) - Lee, Inhye; Choi, Soobin; Lee, Sumin; Soh, Moon-Soo
ABSTRACT: Light is an important environmental cue, causing a high degree of developmental plasticity in higher plants. The outcome of light-regulated developmental response is determined by not only photo-sensory systems but also endogenous physiological contexts in plants. KARRIKIN-INSENSITIVE2 (KAI2) functions as a receptor of karrikin and endogenous, as yet to be identified, KAI2 ligand (KL). The loss-of-function of KAI2 caused light-hyposensitive photomorphogenesis, affecting the expression light-responsive genes under the light conditions. However, it remains still unclear how KAI2-KL signaling interacts with light-signaling. Here, we show that the ply2 mutation, a severe loss-of-function allele of KAI2 affected the expression of a subset of light-responsive genes, irrespectively of light condition. The results implied that the overlapping set of light- and KAI2-responsive genes may serve as an integrating node between light- and KAI2-KL signaling. Further, the results of double mutant analyses between the ply2 mutant and mutants of CONSTITUTIVELY PHOTOMORPHOGENIC1 ( COP1) or LONG HYPOCOTYL IN FAR-RED ( HFR1) implicated that KAI2-KL signaling acts at downstream of COP1, largely independently of HFR1. Together, these results suggest that KAI2-KL signaling intersects with a subset of the light-regulatory network, by which plants adjust their photomorphogenic development.